RUANG KETIGA DALAM PERJUMPAAN NIAS-KRISTEN DAN MINANGKABAU-MUSLIM DI PADANG - Chris Stevany Lombu; Izak Y.M. Lattu; Rama Tulus Pilakoannu (Universitas Gadjah Mada, 2019)
Minangkabau has often been identified as an excluisve ethnic group. In contrast to this view, Nias etnic group in West Sumatera has established a peaceful encounter between Christians and Muslim from both ethnic groups. Nias tribe has been in Padang for about 500 years and encouter Islam as the dominant religion of Minangkabau and other wolrkd religion, namely Christianity. This is something new for the Nias tribe because at first they had animistic beliefs. This article aimes to show the social phenomenon of the meeting between the Nias-Kristen and the Minangkabau-Muslim. Nias community has created a new identity in peacefully bridging the community with Muslim community in Padang. This article explores the formation of new identity among Nias-Padang community as bridging and copping mechanisms to live in a multicultural context that based on Minangkabau-Muslim values in Padang. This new identity heled them to adapt and develop in Padang. This new identity is called Hada Nono Niha Wada (Custom of Nias Padang). This change does not only relate to the name used but also includes component that are in the custom itself. The author employs Homi Bhabha’s third space theory to examine the encounter of Nias Padang-Christianity community and Minang-Muslim host community in Padang. The article shows that through social negotiation, Nias Padang-Christianity community in Padang have formulated new identity that different from that of Nias in the Island of Nias and created the third space to copping with Minangkabau culture-tradition. This negotiation resulted in a custom that had a pattern of openness in accepting differences. The third space provides a place for them to build a mindset that can make them survive as a minority that is able to manage differences into a unity that can be accepted by various parties and living peacefully with the Minangkabau-Muslim community in the greater Padang area.